Tractor ballasting in field transport work - Giedra, Kazimieras; Janulevičius, Algirdas (Transport, 2005)
The article presents the investigation of the interaction of tractor traction force, mass, trailer and tractor mass ratio and wheel slippage. The analysis of the influence of ballast weight and wheel slippage on the fuel consumption under various field and road conditions was carried out. Wheel slippage dependence on the pull force, a weight force utilization coefficient and ratio of the mass of a trailer and tractor were stated and analyzed. The nomogram for operative selection of the optimal ballast weight and its location place is presented when instantaneous wheel slippage is known. The nomogram consists of three parts. In the lower part dependence δ = f (mp / m), (wheel slippage on the ratio of the mass of a trailer and tractor) is placed. In the middle part there is dependence of the tractor mass m made of the expression of the wheel grip weight force utilization coefficient ϕg = Ft / G on the ratio of the mass of a trailer and tractor m=f (mp / m). The upper part is designed for dependence ?mp = f (mp) (transferred mass of tractor Dmp on the rear wheels on the mass trailer mp . The bottom part of the nomogram is connected with the middle part by the common abscissa axle on which the ratio of the mass of a trailer and tractor is placed. The curves of the middle part of the nomogram m = f (mp /m) are connected with the analogical concrete mass trailer values mp , placed in the abscissa axle by intermediate lines.First Published Online: 27 Oct 2010